2014
DOI: 10.1080/0098261x.2013.873290
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Bias in Judicial Performance Evaluations: We Must Do Better Than This

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Although our results show gender bias that is not as pervasive as what other studies have found (Burger 2007;Gill et al 2011;Gill 2014;Tomsich and Guy 2012), it is still cause for concern. This is a particularly acute problem given the dearth of women on the bench in Utah.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…Although our results show gender bias that is not as pervasive as what other studies have found (Burger 2007;Gill et al 2011;Gill 2014;Tomsich and Guy 2012), it is still cause for concern. This is a particularly acute problem given the dearth of women on the bench in Utah.…”
Section: Discussioncontrasting
confidence: 82%
“…Although they do not provide verbatim recommended questions, the guidelines do recommend the use of behavior-based evaluation instruments to "generate more meaningful information about judicial behavior" (American Bar Association 2005, 13). This is where things seem to go wrong (Bernick and Pratto 1995;Elek, Rottman and Cutler 2012;Gill 2014).…”
Section: Issues In Jpe Designmentioning
confidence: 99%
See 3 more Smart Citations